Deficiency in Phylloquinone (Vitamin K1) Methylation Affects Prenyl Quinone Distribution, Photosystem I Abundance, and Anthocyanin Accumulation in the Arabidopsis AtmenG Mutant - Lohmann, Antje; Schöttler, Mark Aurel; Bréhélin, Claire; Kessler, Félix; Bock, Ralph; Cahoon, Edgar B.; Dörmann, Peter (My University, 2006)
Phylloquinone (vitamin K1) is synthesized in cyanobacteria and in chloroplasts of plants, where it serves as electron carrier of photosystem I. The last step of phylloquinone synthesis in cyanobacteria is the methylation of 2-phytyl-1,4-naphthoquinone by the menG gene product. Here, we report that the uncharacterized Arabidopsis gene At1g23360, which shows sequence similarity to menG, functionally complements the Synechocystis menG mutant. An Arabidopsis mutant, AtmenG, carrying a T-DNA insertion in the gene At1g23360 is devoid of phylloquinone, but contains an increased amount of 2-phytyl-1,4-naphthoquinone. Phylloquinone and 2-phytyl-1,4-naphthoquinone in thylakoid membranes of wild type and AtmenG, respectively, predominantly localize to photosystem I, whereas excess amounts of prenyl quinones are stored in plastoglobules. Photosystem I reaction centers are decreased in AtmenG plants under high light, as revealed by immunoblot and spectroscopic measurements. Anthocyanin accumulation and chalcone synthase (CHS1) transcription are affected during high light exposure, indicating that alterations in photosynthesis in AtmenG affect gene expression in the nucleus. Photosystem II quantum yield is decreased under high light. Therefore, the loss of phylloquinone methylation affects photosystem I stability or turnover, and the limitation in functional photosystem I complexes results in overreduction of photosystem II under high light.